Factors that influence treatment-seeking expectations in response to infectious intestinal disease: Original survey and multinomial regression. Issue 4 (April 2020) - Brainard, Julii; Weston, Dale; Leach, Steve; Hunter, Paul R.
Abstract: Background: Infectious intestinal disease affects 25% of the UK population annually; 1 in 50 affected people consult health professionals about their illness. Aims: We tested if anticipated treatment-seeking decisions for suspected infectious intestinal disease could be related to emotional response, tolerance of symptoms, or beliefs about the consequential benefits and harms of seeking treatment (or not). Methods: Questionnaire survey of adults living in the UK with statistical analysis of responses. A vignette was presented about a hypothetical gastrointestinal illness. People stated their emotional reactions, expected actions in response and beliefs about possible benefits or harms from seeking treatment (or not getting treatment). Multinomial regression looked for predictors of anticipated behaviour. Results: People were inclined to consult a GP when they believed that seeking treatment would be beneficial and that its absence would be harmful. Seeking treatment was less anticipated if the condition was expected to improve quickly. Respondents were also more likely to consult if they strongly disliked fever or headache, and/or if the illness made them feel anxious or angry. Treatment-seeking (or lack of it) was not linked to harms from treatment-seeking, other specific symptoms and emotional responses. Conclusion: It was possible to link anticipated treatment-seeking behaviour to specific factors: expected prognosis, perceived benefits of seeking treatment, some emotions and some specific symptoms.